Menggunakan COBIT 2019 GMO dalam Perancangan Pengelolaan Layanan TI untuk Transformasi Digital ReinsurCo - Naufal Rahmadaffa Ariekananda; Rahmat Mulyana; Fitriyana Dewi (STMIK Budi Darma, 2023)
In the context of the digital technology implementation in the Indonesian insurance sector, organization such as ReinsurCo is required to accelerate the digital transformation (TD) process to remain competitive. Even though there are often obstacles in the implementation of TD due to ineffective management of IT services, ReinsurCo as a BUMN supervised by the OJK must comply with regulations such as PER-2/MBU/03/2023 and the 2021-2025 Financial Services Sector Master Plan which emphasizes TD. This study aims to identify governance & management objectives (GMO) of IT service management required by ReinsurCo, develop recommendations for optimizing GMOs based on evaluating the gaps of the seven components of current and target capabilities, and design essential improvements to GMOs based on the recommendations that have been prepared. This research involved five DSR steps: problem description, requirements specification, design and development, demonstration, and evaluation. Data was collected through semi-structured interviews and triangulation of internal documents. Analysis using COBIT 2019 Governance and Management Objectives (GMO), the application of design factors, focus areas, and TKTI mechanisms that influence TD resulted in three priority GMOs: DSS04 Managed Continuity, APO11 Managed Quality, and DSS06 Managed Business Controls. A gap evaluation was carried out to produce recommendations that served as a guide for ReinsurCo in implementation and increased GMO by an average of 0.2 (6.1%). This research contributes to the understanding of IT service management, which is a priority to support TD, the benefits are especially for ReinsurCo in achieving strategic planning success and the insurance industry